IMPLEMENTASI RECHTSVINDING YANG BERKARAKTERISTIK HUKUM PROGRESIF - Hakim, Muh Ridha (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2016)
The fundamental purpose of law is to create justice, legal certainty and utility. The contradiction between justice and legal certainty are dilemmatic for law enforcement officer. The legal certainty side is easier to be applied so that it neglect the justice itself. The law principle is unhierarchical, thus there is no superior principle which can ignore the other principle. The relevance of the application of legal principles is based on the situation in legal issues. Responding to these challenges appear paradigm of progressive law that the law is a scheme that is not final, it continues to move, to change, it follows the dynamics of human life. Therefore, the law is not seen as something that lives in a stagnation. Law is born from provision living in the society (ibi societas ibi ius). On that basis, the law must continue to be dissected and explored through progressive efforts to reach the ultimate truth for the sake of justice.Keywords : Rechtsvinding, Progressive Law